Effects of external load magnitude and carriage techniques on dynamic stability and work performance during fatigued rescue sprint tasks in firefighters - Jiang, Enmeng; Shi, Yan; Zhang, Xinxin; Liu, Weiguo (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThis study aims to investigate the effects of different external load magnitudes and carrying techniques on dynamic stability and work performance during fatigued rescue sprint tasks in firefighters, thereby providing theoretical and practical support for injury prevention and performance enhancement in firefighting rescues.MethodsA total of 126 professional healthy male firefighters performed 30-m rescue sprints under simulated fatigue in a 3 × 3 two-factor experimental design combining three external load magnitudes (10 kg, 20 kg, 30 kg) and three carrying techniques (shoulder-carry, bosom-carry, hand-carry).ResultsExternal load magnitude had no significant effect on margin of stability in the medial and lateral directions (MoSml) (P > 0.05), but the margin of stability in the anterior and posterior directions (MoSap) was significantly lower under 10 kg load tasks compared to 20 and 30 kg loads (P < 0.05). The hand-carry technique significantly increased MoSap (P < 0.05) but significantly reduced MoSml (P < 0.05). For 20 kg loads, hand-carrying resulted in significantly increased MoSml compared to 10 and 30 kg tasks (P < 0.05), while bosom-carrying with 10 kg loads or shoulder-carrying with 20 kg loads significantly reduced MoSml (P < 0.05). Center of mass (CoM) work was significantly higher under 20 kg load tasks (P < 0.05). It was also significantly higher when using the hand-carry technique (P < 0.05), particularly when hand-carrying 20 kg loads (P < 0.05). Both external load magnitude and carrying technique significantly affected hip joint work (P < 0.05). Hip joint work was significantly higher under 10 kg loads (P < 0.05), and significantly greater when using hand-carrying compared to bosom-carrying (P < 0.05).ConclusionIt is recommended that firefighters choose carrying techniques based on specific load conditions: avoiding hand-carrying moderate loads, while shoulder carry for moderate to large loads, and bosom carry for small loads. Additionally, hip joint function training should be emphasised in daily routines to improve body control, reduce injury risk during rescue tasks, and enhance overall task performance.